Analysis of ISO 9001: 2015 Quality Management System Implementation on Customer Satisfaction with Service Quality: A Short Narrative - Hafiza; Sa'ajiz, Muhammad (International Journal of Social and Management Studies, 2023)
The purpose of writing this article is a narrative literature review of 3 (three) articles that discuss the Analysis of ISO 9001: 2015 Quality Management System Implementation on Customer Satisfaction with Service Quality, aiming to identify and summarize previously published articles without any criticism for the articles reviewed. The results of the review indicate that there is a significant relationship between customer satisfaction with service quality and the use of quality management systems, as well as a significant relationship between service quality and the use of quality management systems. Implementation of the Quality Management System has a weak effect on Participant Satisfaction. The main objective of ISO 9001 implementation is to increase customer satisfaction both external and internal, including students as the main users of organizational services as external customers.